Receptor antagonist and selective agonist derivatives of mouse interleukin-2. - Zurawski, S M (1992)
Mouse interleukin-2 (mIL-2) proteins with substitutions at two residues (D34 and Q141) that interact specifically with different signalling subunits (respectively, beta and gamma) of the IL-2 receptor (IL-2R) were examined using several in vitro cellular assays. Proteins with specific substitutions at both residues were partial agonists and their maximal responses varied widely in different IL-2-responsive cell types. Two of these cell types had comparable numbers of IL-2R and similar affinities for wild-type mIL-2 and mutant mIL-2 proteins. However, the more responsive cell type had 'spare' IL-2R. Various mIL-2 proteins with substitutions at Q141 had modest defects in IL-2R-binding and were potent antagonists of native mIL-2 action. Proteins with bulky or basic substitutions at residue D34 were weak antagonists due to severely reduced IL-2 binding and their reduced binding paralleled their defects in IL-2R activation. Our results suggest that interaction of mIL-2 with IL-2R beta is more important for binding than activation and that the converse holds for mIL-2 interaction with IL-2R gamma. Also genetic manipulation of the interaction of IL-2 with IL-2R beta and IL-2R gamma has led to the discovery of potentially useful IL-2 antagonists and selective agonists.